2020
DOI: 10.18488/journal.61.2020.81.149.157
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Roundtable Technique Based on Process Approach to Promote the Students Writing Achievements in Foreign Language Setting

Abstract: This study investigated whether students" writing achievements could increase using a modified roundtable technique based on the process approach and to find out what aspects of writing significantly increase. A quantitative study in the form of preexperimental design was conducted which involved 21 tenth grade students of a 1 Pekalongan-Lampung province senior high school 1 in Indonesia. The overall obtained pre-and post-test writing data were compared through the Paired sample ttest both in the overall sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Furthermore, the qualitative analysis of the semi-structured interviews revealed that learners in the experimental group considered applying the roundtable technique to paragraph writing helped to develop their writing by developing writing components (grammar, vocabulary, organization, content, and mechanism) while incorporating all four stages of writing. This conforms with the previous literature (Fauziah et al, 2020;Fitri et al, 2017;Flora et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the qualitative analysis of the semi-structured interviews revealed that learners in the experimental group considered applying the roundtable technique to paragraph writing helped to develop their writing by developing writing components (grammar, vocabulary, organization, content, and mechanism) while incorporating all four stages of writing. This conforms with the previous literature (Fauziah et al, 2020;Fitri et al, 2017;Flora et al, 2020).…”
Section: Discussionsupporting
confidence: 94%
“…Several empirical studies have proven the impact of using the round table in paragraph writing in foreign ESL/ English as a Foreign Language (EFL) context. Flora et al (2020) concluded that a modified roundtable can increase students' paragraph writing skills as the round table technique enables students to use the target language and share their ideas at every step of writing, and it can be illustrated as follows.…”
Section: Introductionmentioning
confidence: 99%
“…There was some previous research. The research was conducted by Flora et al (2020), Sinaga (2017) & Urunami et al (2017). These researches used Roundtable Technique to improve students' writing ability.…”
Section: Previous Researchmentioning
confidence: 99%
“…By addressing the issues that students encounter when writing descriptive texts, this technique is anticipated to make learning environment more engaging. Researchers used this technique because there are evidences that have been done by previous researchers who reported it in journals that used roundtable technique (Flora et al, 2020;Sinaga, 2017;Urunami et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the stages of the Process Approach could effectively help students to learn how to write a text successfully since the teacher gave them clear instructions on how to complete the activity at each stage of the writing process (Flora, Cahyadi, and Sukirlan, 2020). Hassan and Akhan (2020) also found that the Process Writing Approach has a statistically significant positive influence on writing performance because it emphasized the document creation phase or all of the fundamental aspects of writing.…”
Section: There Is Significant Improvement Of Students' Writing Achiev...mentioning
confidence: 99%